Magnetic resonance imaging of male and female genitals during coitus and female sexual arousal. Issue 7225 (18th December 1999) - Schultz, Willibrord Weijmar; van Andel, Pek; Sabelis, Ida; Mooyaart, Eduard
Abstract: Objective: To find out whether taking images of the male and female genitals during coitus is feasible and to find out whether former and current ideas about the anatomy during sexual intercourse and during female sexual arousal are based on assumptions or on facts. Design: Observational study. Setting: University hospital in the Netherlands. Methods: Magnetic resonance imaging was used to study the female sexual response and the male and female genitals during coitus. Thirteen experiments were performed with eight couples and three single women. Results: The images obtained showed that during intercourse in the "missionary position" the penis has the shape of a boomerang and 1/3 of its length consists of the root of the penis. During female sexual arousal without intercourse the uterus was raised and the anterior vaginal wall lengthened. The size of the uterus did not increase during sexual arousal. Conclusion: Taking magnetic resonance images of the male and female genitals during coitus is feasible and contributes to understanding of anatomy.